Light-regulated nucleo-cytoplasmic partitioning of phytochromes - Kevei, Eva (Journal of experimental botany, 2007)
Phytochrome photoreceptors regulate development, growth, and fitness throughout the entire life-cycle of plants, from seed germination to flowering, by regulating expression patterns of approximately 10-30% of the entire plant transcriptome. Identification of components and elucidation of the molecular mechanisms underlying phytochrome-controlled signal transduction cascades have therefore attracted considerable attention. Phytochrome-controlled signalling is a complex cellular process; it starts with the light-induced intramolecular conformational change of the photoreceptor and includes regulated partitioning and degradation of signalling components and of the photoreceptors themselves. In this review, the data available about light quality- and quantity-dependent nucleo-cytoplasmic partitioning of phytochromes is summarized and the possible function of phytochrome-containing nuclear complexes, termed nuclear bodies, in red/far-red light-induced signalling is discussed